Mercosul and regional development in Brazil: a gravity model approach - Paulo C. de Sá Porto (Universidade de São Paulo, 2002)
This paper assesses the impact of the Mercosul Preferential Trade Agreement onBrazil’s regions by means of a gravity model, extended to include dummy variables for Mercosul and for a Brazilian region. The results show that the most significant regional impacts of Mercosul were onBrazil’s Southern and Southeastern regions, whereas the North, Northeast and Center-West regions benefited much less from Mercosul in the period from 1990 to 1998. These results suggest that Mercosul may be aggravating regional disparities inBrazil.